2003
DOI: 10.1038/ni1012
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of cytokine signaling and immunity

Abstract: The suppressors of cytokine signaling (SOCS) and cytokine-inducible SH2 protein are key physiological regulators of the immune system. Principally, SOCS1 and SOCS3 regulate T cells as well as antigen-presenting cells, including macrophages and dendritic cells. Here we review the function of SOCS1 and SOCS3 in innate and adaptive immunity, with particular emphasis on the relationship between immune regulation and SOCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
492
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(504 citation statements)
references
References 78 publications
10
492
1
1
Order By: Relevance
“…SOCS1 is induced by various cytokines including interferon (IFN)-g, interleukin-4, TNF-a, as well as growth hormones, and downregulates the signals induced by these cytokines in a feedback loop. However, recent studies have indicated that SOCS1 plays diverse roles in cell growth, differentiation, innate immunity, inflammation and apoptosis (Kinjyo et al, 2002;Kubo et al, 2003;He et al, 2006). For example, SOCS1 may suppress the development and/or progression of hepatocellular carcinoma and hematopoietic malignancies (Yoshida et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOCS1 is induced by various cytokines including interferon (IFN)-g, interleukin-4, TNF-a, as well as growth hormones, and downregulates the signals induced by these cytokines in a feedback loop. However, recent studies have indicated that SOCS1 plays diverse roles in cell growth, differentiation, innate immunity, inflammation and apoptosis (Kinjyo et al, 2002;Kubo et al, 2003;He et al, 2006). For example, SOCS1 may suppress the development and/or progression of hepatocellular carcinoma and hematopoietic malignancies (Yoshida et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…SOCS1 has been shown to regulate the sensitivity of pancreatic islet cells toward the TNF-a-induced cytotoxicity mediated by p38 MAPK (Chong et al, 2002). In addition, SOCS1 may act as a modulator of apoptosis to ensure controlled survival and apoptosis during pregnancy and involution, respectively (Kubo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…SOCS4-7 are each composed of a long N-terminal region of over 200 amino acids, whereas CIS and SOCS1-3 have a short N-terminal region of less than 50 amino acids [4,5]. SOCS proteins with a short N-terminal domain have been extensively studied, and are disease-associated [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…One molecule that is important for the induction of tolerance and CD4 + regulatory T cells is the suppressor of cytokine signalling 3 (SOCS3), 21 an antagonist of MF activation, which can be down-regulated by IL-15 in IL-15MF and in IL-15 tg MF (Fig. 4a).…”
Section: Long-term Il-15 Exposure Suppresses Negative Regulators Of Mmentioning
confidence: 99%